“I don’t know what it means to be Australian”: Exploring Australian Identity Conceptualisations, Lived Experiences and Preferences - Farrugia, Jack Peter (Curtin University, 2023)
Social unrest is emerging in Australia due to the continued promotion and endorsement of exclusive constructions of Australian identity. This research comprised four studies to explore Australian identity conceptualisations, lived experiences, and preferences in consideration of unique contemporary issues. Overall, the findings from this research highlight what is needed to improve the construction and promotion of inclusive Australian identity, in hopes that ongoing, problematic, and damaging issues relating to social conflict will diminish over time.